Photoreceptor Proteins Initiate Microglial Activation via Toll-like Receptor 4 in Retinal Degeneration Mediated by All-trans-retinal - Kohno, Hideo (American Society for Biochemistry and Molecular Biology, 2013)
Although several genetic and biochemical factors are associated with the pathogenesis of retinal degeneration, it has yet to be determined how these different impairments can cause similar degenerative phenotypes. Here, we report microglial/macrophage activation in both a Stargardt disease and age-related macular degeneration mouse model caused by delayed clearance of all-trans-retinal from the retina, and in a retinitis pigmentosa mouse model with impaired retinal pigment epithelium (RPE) phagocytosis. Mouse microglia displayed RPE cytotoxicity and increased production of inflammatory chemokines/cytokines, Ccl2, Il1b, and Tnf, after coincubation with ligands that activate innate immunity. Notably, phagocytosis of photoreceptor proteins increased the activation of microglia/macrophages and RPE cells isolated from model mice as well as wild-type mice. The mRNA levels of Tlr2 and Tlr4, which can recognize proteins as their ligands, were elevated in mice with retinal degeneration. Bone marrow-derived macrophages from Tlr4-deficient mice did not increase Ccl2 after coincubation with photoreceptor proteins. Tlr4(−/−)Abca4(−/−)Rdh8(−/−) mice displayed milder retinal degenerative phenotypes than Abca4(−/−)Rdh8(−/−) mice. Additionally, inactivation of microglia/macrophages by pharmacological approaches attenuated mouse retinal degeneration. This study demonstrates an important contribution of TLR4-mediated microglial activation by endogenous photoreceptor proteins in retinal inflammation that aggravates retinal cell death. This pathway is likely to represent an underlying common pathology in degenerative retinal disorders.